Influence of Compost on the Growth of Seedling of Mahogany (Swietenia macrophylla King.) Used in Land Mine Gold (Tailings) - Basuki Wasis; Agustina Sandrasari (Jurnal Silvikultur Tropika, 2011)
Tailing is one form of waste produced in large quantities in the gold mining activities are nutrient poor. Therefore it is necessary for land revegetation in these tailings. Revegetation activities must be conducted on former mining land, but often encounter obstacles that revegetation efforts are quite heavy. The success of revegetation on land that is dominated by tailings require plants that are able to adapt as mahagony seedling (Swietenia macrophylla), which has the potential if planted in dry soil as the soil tailings. This study used a complete randomized design. The results showed 30 grams of compost fertilizer effect is very real influence with the percentage growth of 40.70% against the control with an average growth of 6.81 cm.